Postoperative cognitive dysfunction and cerebral microembolization during coronary artery bypass surgery under conditions of artificial circulation - Dmytro Radiushin (Kazimierz Wielki University, 2019)
Damage to the brain is one of the first places in the list of postoperative complications in cardiosurgical operations. In modern scientific literature, many mechanisms of damage to the brain in cardiosurgical patients, operated under the conditions of artificial circulation, are discussed. The lack of a common opinion in this issue justifies the need for additional research. The aim of the study was to analyze the volume of cerebral microembolization in the basin of the middle cerebral arteries (MCA) during coronary artery bypass grafting (CABG) in conditions of artificial circulation (AC), and to investigate the relationship between cerebral microembolization and the development of postoperative cognitive disorders. The study included 34 patients (19 men and 15 women) who underwent CABG using AC. Monitoring of cerebral blood flow during the operation was carried out on the apparatus "Angiodin 2K" (Bios, Russia). Assessment of the cognitive status of patients was carried out using verbal and nonverbal tests. Evaluation was carried out twice, before surgery and on the fifth day after the operation. Criteria for diagnosis of postoperative cognitive dysfunction (POCD) showed a decrease in the results of testing by 10% or more with a full study in two tests and more, and a decrease of 2 points or more in the tests of MOS and MMSE. These data indicate that in all patients after aortocoronary shunting under the conditions of artificial circulation, microembolization of the cerebral blood flow is determined, and in the amount of more than 800 microemboli, results in a clinically pronounced impairment of brain function in the early postoperative period (r = 0.78 p